Design of Computational Model for Cyanobacterial Pollutant Diffusion Change in Chaohu Lake of China Based on Large Data - Junping Yao; Guilan He (Discrete Dynamics in Nature and Society)
Cyanobacteria in Chaohu Lake multiply rapidly and diffuse in large quantities every summer, which has a serious impact on the normal life of the surrounding residents and the local economic development. Therefore, it is urgent to control the cyanobacterial pollutants in Chaohu Lake. In this context, in order to improve the scientificalness and feasibility of control measures, it is an important prerequisite and condition to grasp the change of cyanobacterial pollutant diffusion in Chaohu Lake. For this reason, a computational model for cyanobacterial pollutant diffusion in Chaohu Lake, China, was designed based on the relevant large data. The design of the model is divided into three parts: the first part builds an area calculation model to analyze the change of cyanobacterial pollutant diffusion area; the second part builds a concentration calculation model to analyze the change of cyanobacterial pollutant concentration; and the third part combines the previous two to build a diffusion change calculation model to analyze the rule of cyanobacterial pollutant diffusion change in Chaohu Lake. In order to verify the feasibility and validity of the model, simulation experiments were carried out. The results show that, under the large data related to cyanobacteria pollution in Chaohu Lake, China, from May to August 2017, the calculation model is used to calculate the cyanobacteria pollutant diffusion change. The data obtained are basically consistent with the actual situation, which proves the feasibility and validity of the model. This provides data support for the cyanobacteria pollution control in Chaohu Lake and improves the efficiency and effect of the control.